Pola Konsumsi Pangan pada Ketahanan Rumah Tangga Petani Desa Nyawangan, Kabupaten Kediri - Berlian Feby Wijayanti; Hamidah Hendrarini; Nisa Hafi Idhoh Fitriana (Universitas Hamzanwadi, 2026)
Food security for farming households is an important issue in agrarian areas that still face limited access and low-quality food consumption. This research aims to analyze the consumption patterns and food security levels of farmer households in Nyawangan Village, Kras District, Kediri Regency. This research uses a quantitative descriptive method thru surveys of 56 farmer households selected by simple random sampling. Primary data were collected thru structured interviews using a 24-hour food recall and a household expenditure questionnaire. Analysis using the Energy Sufficiency Level (ESL) indicator, Expected Food Pattern (EFP), Food Expenditure Proportion (FEP), and cross-classification. The results show an average ESL of 83.8% (insufficient category) and an EFP score of 69.95, indicating a lack of diversity in consumption, still dominated by cereals. The average FEP of 55.96% indicates relatively high food expenditure. As many as 48.21% of households were classified as food secure, while 30.36% were in a state of food insecurity and vulnerability. It is concluded that food security is not yet fully stable due to low consumption diversity and economic pressure. Therefore, food diversification based on local potential, nutrition education, and strengthening the economic resilience of farmers' households is highly necessary.